A 31P nuclear magnetic resonance study of phosphate levels in roots of ectomycorrhizal and nonmycorrhizal plants of Castanea sativa Mill. - Martins, Anabela (2011)
31P-Nuclear Magnetic Resonance (NMR) was used to assess phosphate distribution in ectomycorrhizal and nonmycorrhizal roots of Castanea sativa Mill. as well as in the mycorrhizal fungus Pisolithus tinctorius in order to gain insight into phosphate trafficking in these systems. The fungus P. tinctorius accumulated high levels of polyphosphates during the rapid phase of growth. Mycorrhizal and nonmycorrhizal roots accumulate orthophosphate. Only mycorrhizal roots presented polyphosphates. The content in polyphosphates increased along the 3 months of mycorrhiza formation. In mycorrhizal roots of plants cultured under axenic conditions, the orthophosphate pool decreased along the culture time. In nonmycorrhizal roots the decrease in the orthophosphate content was less pronounced. The level of orthophosphate in mycorrhizal roots was significantly lower than in nonmycorrhizal ones, which indicates that this system relies upon the fungal polyphosphates as a major source of phosphate.